The Impact Mechanism of Green Finance on Carbon Emission Reduction An Empirical Analysis Using China's Provincial Panel Data - Li, Susu; Liang, Jingyi; Jiao, Ping (Innovative Applications of AI, 2024)
By utilizing the provincial panel data between 2010 and 2021 of China, the present research examines the mechanism whereby green financial development influences carbon emission reduction by applying the fixed and intermediary effect models. It is found that: (1) Green financial development produces an inhibitory influence over carbon emission intensity, implying that it can promote carbon emission reduction. The robustness test, which includes the instrumental variable method and the substitution of explained variables, is still valid. (2) Among these, the green finance development especially exerts a noteworthy influence over carbon abatement in western regions. (3) The influence of green finance development over carbon emission intensity is somewhat mitigated by green technology innovation and upgrading of regional industrial structure. As a result, it is recommended that all localities formulate locally-tailored policies of green financial development, and encourage enterprises to actively use green technology innovation means to promote green transformation, thereby facilitating the industrial structure upgrading and stimulating further release of green financial potential to enhance the carbon abatement efficiency.